Student Mobilities - Alves, Elisa (2022)
Student mobility or student migration? The international (and internal) movement of students displays an equivocal terminology, although the editor of this volume, in presenting us with the title of our chapter, prefers the broader term ‘mobilities’ in contrast to the titles of the other chapters in this section, which are all forms of ‘migration’. So why is it that, when students move—either internationally, or within their own countries—they are not usually seen as ‘migrants’, but as something else? This chapter aims to reflect further on the emergence of the twin concepts of migration and mobility as applied to the movement of students—how the concepts have been deployed in various situations and how they have been conditioned (or not) by different theoretical and methodological approaches to the subject of students’ spatial moves. Given that migration and mobility both connote geographical movement across space and over a range of periods of time, we ‘play’ with this notion of movement and propose the alternative term of student movementation. The chapter is structured in three parts. The first develops the definitional, terminological, and conceptual discussion introduced above. In the second section we survey the various directions in past and ongoing research on international student movementation. The conclusion reflects on gaps in our knowledge in this field. Throughout our account we try to give evidence of the empirical richness of research on students’ international moves by referring to a wide body of literature.